METHOD OF RECONSTRUCTION OF THE FRAME STREAM WITH THE SETTING INTEGRITY LEVEL OF THE VIDEO INFORMATION - Бараннік, В. В.; Акімов, Р. І. (Science-based technologies, 2013)
It is shown that the key access method on getting video information in dynamic regime is based on the use of remote means of collection and access to information resources. It is proved that the reduction of compressed video bit rate is achieved by significantly reducing the integrity of the video and increase its processing delays. It is states the developing a method of reconstruction of the video stream based on: identification levels of the hierarchical structure of the compressed code stream; encapsulation and decoding biadic codes of basic elements interframe aperture of P-frames package; approximation interframe apertures on its basic elements; assembling P-frames with individual inter apertures; restoring the original frames using information on the base frame and matrix signs. It is proved that the technology created by processing video is unique and can realy reduce the amount of distortion introduced by comparison with the technology based on MPEG standard, which ultimately increases the integrity of video information resource.